Law Enforcement Against Mill Criminal Activities During The Implementation Of Ppkm In West Java - Yani Swakotama; Joko T. Suroso; Edy Santoso (LEGAL BRIEF, 2022)
The implementation of Community Activity Restrictions (PPKM) in its implementation is still not effective based on data, that as of April 8, 2021 the number of people who were positively exposed to Coronavirus Disease-19 (Covid-19) spread across various provinces in Indonesia, amounting to 1,552,880 people, with recovery infected patients amounted to 1,399,382 people and the number of deaths was 42,227 people in Indonesia. In addition, there are cases of PPKM violations during the Covid-19 pandemic on West Java Provincial Regulation Number 05 of 2021 concerning the Implementation of Peace, Public Order and Community Protection, as happened in the jurisdiction of the Purwakarta District Court which has decided the case with Decision Number 19 /Pid.C/2021/PN.Pwk. jo. Decision Number 28/Pid.C/2021/PN.Pwk. The method used is normative juridical with descriptive analytical research specifications with data collection techniques carried out through document studies and interviews which are then analyzed by qualitative normative methods without using mathematical formulas and numbers. Based on the results of the research, that in practice in the field it is resolved through the Court although it is still not effective.